The Intricateness of Adaptation of Literature to Film in Today’s Crisscrossed World - Pasopati, Rommel Utungga; Suyaji, Fransisca Irnidianis Magdalena; Kirana, Kheista Sasi; Ramadhani, Riska Dewi; Wijaya, Kusuma (Journal Corner of Education, Linguistics, and Literature, 2024)
This paper investigates the realities of literature adaptation to film in today’s world of literary criticism. People enjoy motion pictures and compare them with its original textual Literature. By focusing on literary criticism theories, this article explains modern to postmodern aesthetic points, especially in the era of definitions in romanticism, reflectionism and its auto, empiricism until pragmatism, and the age of language beyond communication. Through those former points, the adaptation of Literature to film brings in a wider point: the world itself. The adaptation is shown to broaden concepts and interpretations among writers, directors, and also audiences. Every aspect is so active to interpret in today's crisscrossed world that meanings vary from critical and evaluation perspectives. The adaptation is not about merely fixed definitions or even market orientations but open meanings on dialogues among realities. Any measurement from Literature or film is never enough to compare adaptation to its original form since it is located between individualities and societies. In conclusion, the adaptation of Literature should indicate that dominations must be minimized by maximizing hospitality of differences.